Response of the middle atmosphere to anthropogenic and natural forcings in the CMIP5 simulations with the Max Planck Institute Earth system model. (6th March 2013) - Schmidt, H.; Rast, S.; Bunzel, F.; Esch, M.; Giorgetta, M.; Kinne, S.; Krismer, T.; Stenchikov, G.; Timmreck, C.; Tomassini, L.; Walz, M.
Key Points Middle atmosphere features of the MPI‐ESM and external data are described Middle atmosphere response to climate forcing in CMIP5 simulations is discussed Future middle atmosphere evolution depends strongly on the emission scenario